OPTIMASI SINTESIS BIOSURFAKTAN LAURIL AMIDA DARI ASAM LAURAT DAN DIETANOLAMINA MENGGUNAKAN PELARUT HEXANE DAN ENZIM LIPASE TERIMOBILISASI - Denny Samuel Silaen; Tjahjono Herawan; Zuhrina Masyithah; Hiskia Arapenta Ginting (Jurnal Teknik Kimia USU, 2017)
Lauril amide is one of nonionic surfactant and has potency to become an ecofriendly surfactant. The main problem on lauril amide synthesis is the low conversion of lauric acid. Optimation of lauril amide synthesis is done with three variabels which give influence of amidation reaction. One stage amidation was done by reacting lauric acid with diethanolamine using catalyst Novozyme 435® with substrate ratio lauric acid:diethanolamine 1:1; 2:1; 3:1; 4:1; 5:1, amount of catalyst 1,8; 4; 7; 10; 11,8% from lauric acid total amount, solvent ratio 0; 1:1; 2:1; 3:1; 4:1 from lauric acid total amount and reacted for 24 hours with temperature reaction 55oC and 500 rpm. Product is separated from catalyst using filtration method and then purified by washing with acetone and heated at temperature of 90 oC to remove solvent. Product has been analyzed with acid value to obtained percent conversion of lauril amide, determine of Hydrophilic Liphophilic Balance value, spectroscopy Fourier Transform Infrared and determine of critical micelle concentrasion. Percent conversion optimum has obtained 86,16% at condition substrate ratio 1:1, enzyme concentration Novozyme 435® 7% and solvent ratio 2:1. Analysis result of lauril amide surfactant gave the hidrophile liphophile balance value about 11,93, it means that lauril amide surfactant can be used as emultion oil in water.